The ACT-ONE trial, a multicentre, randomised, double-blind, placebo-controlled, dose-finding study of the anabolic/catabolic transforming agent, MT-102 in subjects with cachexia related to stage III and IV non-small cell lung cancer and colorectal cancer: study design - Stewart Coats, Andrew J.; Srinivasan, Venkatesan; Surendran, Jayaraman; Chiramana, Haritha; Vangipuram, Shankar R. K. G.; Bhatt, Nirajkumar N.; Jain, Minish; Shah, Sandip; Ali, Irfhan A. B. H.; Fuang, Ho G.; Mat Hassan, Mohd. Zailani; Beadle, John; et al. (Springer, 2011)
Aims Cachexia, the wasting disorder associated with a wide range of serious illnesses including cancer, is a major cause of morbidity and mortality. There is currently no widely approved therapeutic agent for treating or preventing cancer-associated cachexia. Colorectal cancer and nonsmall cell lung cancer have relatively high incidences of cachexia, approximately 28% and 34%, respectively. Neurohormonal overactivity has been implicated in the genesis and progression of cachexia and beta receptor antagonism has been proposed as a potential therapy. MT-102, a novel anabolic/catabolic transforming agent, has a multi-functional effect upon three potential pharmacological targets in cancer cachexia, namely reduced catabolism through non-selective β-blockade, reduced fatigue, and thermogenesis through central 5-HT1a antagonism and increased anabolism through partial β-2 receptor agonism. Methods At least 132 male and female patients, aged between 25 and 80 years with a confirmed diagnosis of late-stage non-small cell lung cancer or colorectal cancer, with cachexia will be randomised to either one of the two MT-102 doses or placebo in a 3:1:2 ratio (MT-102 10 mg BD−1/MT-102 2.5 mg BD/placebo). Patients will continue on study treatment for maximally 16 weeks. The primary endpoint, to be analysed by assigned treatment group, will be body weight change over 16 weeks. For this endpoint, the study has 85% power (0.05% significance level) to detect per 4-week period a mean change of −0.8 kg in the placebo group and 0 kg in the high-dose MT-102 arm. The first patient was randomised in February 2011 and patient recruitment is expected to continue until mid-2012. Perspective The ACT-ONE trial is designed to test whether the anabolic/catabolic transforming agent MT-102 will positively impact on the rate of change of body weight in cancer cachexia, thereby evaluating a novel therapeutic strategy in this hitherto poorly treatable condition. A separate ACT-TWO trial will recruit patients who complete the ACT-ONE trial and remain on randomised double-blind medication. Participants in ACT-TWO will be followed for an additional period with a separate primary endpoint.